1971
DOI: 10.2466/pms.1971.32.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Size Estimation in Schizophrenia: Some Additional Controls

Abstract: Size estimation was studied in 14 hospital aides and the following four groups of 14 male schizophrenics: acute good premorbid paranoid, acute poor premorbid nonparanoid, chronic good premorbid paranoid, and chronic poor rem morbid nonparanoid. Unlike previous studies: (1) Ss were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Silverman's (1964a) alternative criteria (early term < 3 years length of hospitalization, long term > 6 years length of hospitalization) were based on his analysis of studies which suggested that these criteria identified patient subgroups which were quite different on perceptual and cognitive measures. These groups also differed in other important ways (e.g., phenothiazine treatment status, premormid adjustment, and paranoid status) and the theoretical propositions associated with these chronicity criteria have subsequently had a mixed validity history (Kopfstein & Neale, 1971;Neale & Cromwell, 1970;Neale, Davis, & Cromwell, 1971). The meaningfulness of these criteria are thus also uncertain.…”
Section: Construct Of Chronicitymentioning
confidence: 99%
“…Silverman's (1964a) alternative criteria (early term < 3 years length of hospitalization, long term > 6 years length of hospitalization) were based on his analysis of studies which suggested that these criteria identified patient subgroups which were quite different on perceptual and cognitive measures. These groups also differed in other important ways (e.g., phenothiazine treatment status, premormid adjustment, and paranoid status) and the theoretical propositions associated with these chronicity criteria have subsequently had a mixed validity history (Kopfstein & Neale, 1971;Neale & Cromwell, 1970;Neale, Davis, & Cromwell, 1971). The meaningfulness of these criteria are thus also uncertain.…”
Section: Construct Of Chronicitymentioning
confidence: 99%